2018
DOI: 10.1126/science.aau0747
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric 14 C/ 12 C changes during the last glacial period from Hulu Cave

Abstract: Paired measurements of 14C/12C and 230Th ages from two Hulu Cave stalagmites complete a precise record of atmospheric 14C covering the full range of the 14C dating method (~54,000 years). Over the last glacial period, atmospheric 14C/12C ranges from values similar to modern values to values 1.70 times higher (42,000 to 39,000 years ago). The latter correspond to 14C ages 5200 years less than calibrated ages and correlate with the Laschamp geomagnetic excursion followed by Heinrich Stadial 4. Millennial-scale v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 51 publications
(36 reference statements)
5
89
0
Order By: Relevance
“…Different pathways of carbonate dissolution affect the carbon isotope composition of drip water (Hendy, 1971;Fohlmeister et al, 2010;Minami et al, 2015). Carbonate dissolution conditions can be similar in the same cave for the same time period, as deduced by radiocarbon reservoir effects of contemporaneously growing speleothems from the same cave (e.g., Fohlmeister et al, 2012;Lechleitner et al, 2016;Cheng et al, 2018;Riechelmann et al, 2019). Furthermore, modelling studies have shown that slight differences in carbonate dissolution conditions have only a small effect on δ 13 C values (Hendy, 1971;Fohlmeister et al, 2011;Griffiths et al, 2012).…”
Section: Influence Of Carbonate Dissolution Conditionsmentioning
confidence: 99%
“…Different pathways of carbonate dissolution affect the carbon isotope composition of drip water (Hendy, 1971;Fohlmeister et al, 2010;Minami et al, 2015). Carbonate dissolution conditions can be similar in the same cave for the same time period, as deduced by radiocarbon reservoir effects of contemporaneously growing speleothems from the same cave (e.g., Fohlmeister et al, 2012;Lechleitner et al, 2016;Cheng et al, 2018;Riechelmann et al, 2019). Furthermore, modelling studies have shown that slight differences in carbonate dissolution conditions have only a small effect on δ 13 C values (Hendy, 1971;Fohlmeister et al, 2011;Griffiths et al, 2012).…”
Section: Influence Of Carbonate Dissolution Conditionsmentioning
confidence: 99%
“…The occurrence of a higher abundance of Neogloboquadrina pachyderma (dextral), e.g., during warmer intervals, such as the Bölling-Alleröd (B/A), has been challenging to explain. On the other hand, paired measurements of 14 C/ 12 C and 230 Th ages from Hulu Cave stalagmites suggest magnetic field changes have greatly contributed to high atmospheric 14 C/ 12 C values at HS4 and the Younger Dryas (YD) (Cheng et al, 2018). Thus a constant reservoir age ( R = 0) assumed when calibrating foraminiferal radiocarbon dates using CALIB 6 software and the Marine 13 calibration dataset (Reimer et al, 2013) for core CSH1 may cause large chronological uncertainties.…”
Section: Chronostratigraphy Of Core Csh1mentioning
confidence: 99%
“…Cave bear bones from excavation site 2 yielded moderate to low N values suggesting variably low collagen preservation. Radiocarbon data of three samples with relatively high N values indicate that they are probably older than about 50k cal a bp (Cheng et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Cave bear bones from excavation site 2 yielded moderate to low N values suggesting variably low collagen preservation. Radiocarbon data of three samples with relatively high N values indicate that they are probably older than about 50k cal a BP (Cheng et al, 2018). 230 Th/U analyses do not date the bones directly, but allow to narrow down the time interval of cave bear occupation.…”
Section: Assessment Of Age Datamentioning
confidence: 99%